The American democracy - Patterson, Thomas E. (McGraw Hill, 2008)
This comprehensive text is known for its exciting writing style and its positive, forward-looking presentation of the latest developments in scholarship and real-life politics. Through the use of engaging narrative, The American Democracy weaves together theory, information, and examples in ways that highlight key points, make them easy to understand, and capture readers' interest.